2016
DOI: 10.24310/abm.v41i0.2445
|View full text |Cite
|
Sign up to set email alerts
|

Nuevas citas y registros corológicos para la flora bentónica marina del noroeste ibérico. New records and geographical additions for the benthic marine flora of the northwestern Iberia.

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Dictyota cyanoloma was described in 2010, based on specimens from Palamós, NW Mediterranean [56], although the species was first reported from the Iberian Peninsula as D. ciliolata by Rull Lluch et al [57]. The species is widely distributed in the Mediterranean Sea and recent records have proven its expansion to the European Atlantic (Portugal, Galicia, the SW England), and the Macaronesia [56,[58][59][60][61][62][63], while Steen et al [55] reported it from Australia and New Zealand. Steen et al [55] obtained molecular sequence information from historical herbarium samples of Dictyota spp.…”
Section: Case Studies From the Mediterranean Seamentioning
confidence: 99%
“…Dictyota cyanoloma was described in 2010, based on specimens from Palamós, NW Mediterranean [56], although the species was first reported from the Iberian Peninsula as D. ciliolata by Rull Lluch et al [57]. The species is widely distributed in the Mediterranean Sea and recent records have proven its expansion to the European Atlantic (Portugal, Galicia, the SW England), and the Macaronesia [56,[58][59][60][61][62][63], while Steen et al [55] reported it from Australia and New Zealand. Steen et al [55] obtained molecular sequence information from historical herbarium samples of Dictyota spp.…”
Section: Case Studies From the Mediterranean Seamentioning
confidence: 99%